A Chinese EFL student's strategies in graduation thesis writing: An Activity Theory perspective. Issue 61 (January 2023) - Ren, Beibei; Zhu, Wei
Abstract: Against the background of increasing L2 writing strategy research from a sociocultural paradigm in recent years, writing scholarship has been focusing on L2 learners' writing strategies in various writing tasks. Undergraduate students' graduation paper in the Chinese context, however, has yet to receive sufficient attention. Informed by Activity Theory framework (Engeström, 1987, 1999), this paper adopted a case study design and investigated a Chinese undergraduate student's writing strategies in the graduation paper writing activity. Drawing on interviews with the student and the advisor, the student's paper, and supplementary documents (e.g., paper guidelines), this study showed that the student utilized artefact, rule, community, and role mediated strategies to complete the writing task. Contradictions within and beyond the activity system also existed, which constrained the successful mediation of some of the writing strategies and posed challenges to the student's writing activity. Implications for research and pedagogy are discussed.